Determination and stability of some international screening limited drugs in equine blood by LC-MS/MS - CÜCÜ, AYŞEN (ANKARA UNIV PRESS, 2019)
Stability of some international screening limited therapeutic substances for doping control in equine blood has been investigated with a validated method by using LC-MS/MS after chemical hydrolysis with orthophosphoric acid. Whole blood samples were extracted with a WAX cartridge on auto-SPE. Stability test of the drug substances performed at the same time in working solution and matrix at +4 degrees C, -20 degrees C, +20 degrees C in dark and +20 degrees C in light conditions for 1, 2, 3 and 4 weeks. For short-time stability, the effects of 6 h storage at +55 degrees C was also investigated. Repeated data were statistically analyzed with ANOVA. All substances in working solution were stable at -20 degrees C and +4 degrees C. In the blood matrix, higher temperatures (+20 degrees C) in light and dark caused degradation of substances at the end of four weeks and short-term study (P<0.05). In conclusion, these international screening limited substances in blood matrix could be unstable related to temperature and storage time, although in working solution they could be mostly stable in various temperatures for four weeks.
Keywords: Doping control; equine blood; LC-MS/MS; stability; STORAGE-CONDITIONS; TERM STABILITY; DOPING AGENTS; URINE SAMPLES; TESTOSTERONE